NK Cell Function Regulation by TGF-β-Induced Epigenetic Mechanisms - Regis, Stefano; Dondero, Alessandra; Caliendo, Fabio; Bottino, Cristina; Castriconi, Roberta (Frontiers in Immunology, 2020)
TGF-β is a potent immunosuppressive cytokine that severely affects the function of NK cells. Tumor cells can take advantage of this ability, enriching their surrounding microenvironment with TGF-β. TGF-β can alter the expression of effector molecules and of activating and chemokine receptors, influence metabolism, induce the NK cell conversion toward the less cytolytic ILC1s. These and other changes possibly occur by the induction of complex gene expression programs, involving epigenetic mechanisms. While most of these programs are at present unexplored, the role of certain transcription factors, microRNAs and chromatin changes determined by TGF-β in NK cells start to be elucidated in human and/or mouse NK cells. The deep understanding of these mechanisms will be useful to design therapies contributing to restore the full NK function.